Cost-Effectiveness of Lifestyle-Related Interventions for the Primary Prevention of Breast Cancer: A Rapid Review - Bellanger, Martine; Barry, Katharine; Rana, Juwel; Regnaux, Jean-Philippe (Frontiers in Medicine, 2020)
Background In 2018, the global estimate of newly diagnosed breast cancer cases among women totaled 2.1 million. The economic and social burden of breast cancer placed on societies has propelled research analyzing the role of modifiable risk factors as primary prevention methods. Healthy behavior changes, moderated alcohol intake, healthy body weight, and regular physical activity may decrease the risk of breast cancer among women. This review aimed to synthesize evidence on the cost-effectiveness of lifestyle-related interventions for primary prevention of breast cancer in order to answer the question of whether implementing interventions focusing on behavior changes are worth the value for money. Methods A rapid review was performed using search terms developed by the research team. Articles were retrieved from MEDLINE and the Tufts Medical Center Cost-Effectiveness Analysis Registry, with an additional web search in Google and Google Scholar. Comparisons were performed on the cost-effectiveness ratio per Quality-adjusted life year (QALY) between the interventions using a league table, and the likelihood of cost-effective interventions for breast cancer primary prevention was analyzed. Results Six studies were selected. The median cost-effectiveness ratio (in 2018 USD) was $24, 973, and 80% of the interventions had a ratio below $50,000 threshold. The low-fat diet program for postmenopausal women was cost-effective at a societal level, and the physical activity interventions, such as the Be Active Program in the UK, had the best cost-saving results. Eleven of the twenty-five interventions ranked either high or very high as likely to be cost-effective for breast cancer primary preventions. Conclusion Though the review had some limitations with using only few studies, it showed evidence that diet-related and physical activity-related interventions for primary prevention of breast cancer were cost effective. Many of the cost-effective interventions aimed to reduce the risk of NCDs alongside breast cancer.